Unemployment and Structural Inequality in Romania: A Macro-Level Perspective (2002–2024) - Beldiman, Camelia Mădălina (EuroEconomica, 2025)
This study examines the macroeconomic determinants of unemployment in Romania between 2002 and 2024. It aims to identify structural patterns influencing labour market performance in a post-transition context, where inclusive employment remains a key developmental challenge. Prior Work: The research builds upon theories of human capital, segmented labour markets, and structural inequality, responding to gaps in existing studies that either focus on aggregate unemployment or omit the stratifying role of educational attainment and income distribution. Approach: Using a macro-level econometric design, the study employs time-series data and ordinary least squares (OLS) regression to assess the influence macroeconomic determinants on Romania’s general unemployment rate. Results: The findings reveal that income inequality has a statistically significant but negative effect on unemployment, while gross savings and economic growth are not significant predictors. These results suggest structural segmentation in the Romanian labour market and a weak linkage between growth and job creation. Implications: The study has policy relevance for academics, economists, and institutional stakeholders seeking to promote labour market inclusiveness and macro-social equity. Value: This paper provides original empirical insight into how macroeconomic variables influence unemployment in a post-socialist EU economy, challenging conventional assumptions and offering evidence-based directions for structural reform.